2015
DOI: 10.1038/nsmb.3005
|View full text |Cite
|
Sign up to set email alerts
|

A lncRNA regulates alternative splicing via establishment of a splicing-specific chromatin signature

Abstract: Alternative pre-mRNA splicing is a highly cell type-specific process essential to generating protein diversity. However, the mechanisms responsible for the establishment and maintenance of heritable cell-specific alternative-splicing programs are poorly understood. Recent observations point to a role of histone modifications in the regulation of alternative splicing. Here we report a new mechanism of chromatin-mediated splicing control involving a long noncoding RNA (lncRNA). We have identified an evolutionari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
175
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(181 citation statements)
references
References 34 publications
3
175
0
3
Order By: Relevance
“…In humans, KDM2 has two homologues (KDM2A and KDM2B) that demethylate H3K36me2 and repress transcription (41, 42). KDM2A interacts with SUZ12, a component of Polycomb repressive complex 2 (43). Overexpression of KDM2A reduced MLL-dependent transcription and leukemic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, KDM2 has two homologues (KDM2A and KDM2B) that demethylate H3K36me2 and repress transcription (41, 42). KDM2A interacts with SUZ12, a component of Polycomb repressive complex 2 (43). Overexpression of KDM2A reduced MLL-dependent transcription and leukemic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, lncRNAs have been shown to affect AS by different mechanisms, which provides cells with an additional level of complexity to the regulation of gene expression. 38,51,52 Extensive changes in AS of many mRNAs have been reported in EMT. 8,12 In the well-characterized family of FGFRs, it has been reported that FGFR1IIIc and FGFR2IIIb, respective isoforms of FGFR1 and FGFR2, are upregulated and downregulated, respectively, by TGF-β, producing NMuMG cells to be sensitive to FGF-2.…”
Section: Discussionmentioning
confidence: 99%
“…67 lncRNAs influence gene expression by several pathways and are often associated with epigenetic regulation by silencing specific genes 68 and acting as chromatin modulators 69,70 and histone modificators. 52,71 lncRNAs can also alter gene expression through alternative splicing, 72 modulating the rates of RNA polymerase II initiation/elongation, 73 and forming paraspeckles structures. 74 In post-transcriptional levels, lncRNA can act in translation 75 and/or stability of target mRNAs 63 and as decoys for microRNAs, altering protein turnover.…”
Section: Long Noncoding Rnasmentioning
confidence: 99%